Evidence, hierarchies, and typologies: horses for courses - Petticrew, M; Roberts, H (Journal of epidemiology and community health, 2003)
Debate is ongoing about the nature and use of evidence in public healt h decision making, and there seems to be an emerging consensus that th e "hierarchy of evidence" may be difficult to apply in other settings. It may be unhelpful however to simply abandon the hierarchy without h aving a framework or guide to replace it. One such framework is discus sed. This is based around a matrix, and emphasises the need to match r esearch questions to specific types of research. This emphasis on meth odological appropriateness, and on typologies rather than hierarchies of evidence may be helpful in organising and appraising public health evidence.
Keywords: Decision Making; Policy making; Public Health; Public policy